The Analysis of Braess’ Paradox and Robustness Based on Dynamic Traffic Assignment Models - Bai-Bai Fu; Chun-Xue Zhao; Shu-bin Li (Discrete Dynamics in Nature and Society)
The investigation of the paradox and robustness about the traffic network is an important branch of the traffic assignment. In this paper, Braess’ paradox and robustness of the dynamic traffic network are analyzed by the dynamic traffic assignment models. In addition, the relationship of total costs with different traffic assignment models is discussed. The results show that the paradox only occurs in certain range; the robustness of the network and the relationship of total traffic costs are changed as the traffic demand changes, which provides theoretical guidance for the urban transportation planning.